Perbandingan Metode TAM dengan UAT Efisiensi Aplikasi Kehadiran Karyawan Berbasis Android - Mochamad Sofyan; Agus Budiyantara (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The presence of employees in the company refers to their physical availability and mental involvement in carrying out their assigned duties and responsibilities. This includes punctuality, productivity, as well as positive contributions to company culture and achievement of organizational goals. The aim of the research conducted on employee attendance is to show how high the level of efficiency in using the attendance application is by comparing the TAM and UAT methods so that the difference in this concept determines whether employee responses are accepted or not. utilization of this technology, the TAM method is a framework for understanding technology adoption behavior based on user perceptions of usability and ease of use, while the UAT method testing is the process of testing software by end users to ensure suitability to business needs. The final comparison results obtained by the TAM and UAT methods had percentages of 84.69% and 87.38%. which is categorized as good in terms of utilization of attendance applications for employees.